A mechanism-based group psychotherapy approach to aggressive behavior (MAAP) in borderline personality disorder: a multicenter randomized controlled clinical trial - Sigrist, Christine; Bechdolf, Andreas; Bertsch, Katja; Bullenkamp, Robin Pascal; Busse, Martin Gerhard; Darrelmann, Ute gr.; Dempfle, Astrid; Driessen, Martin; Frodl, Thomas; Kersting, Jan-Michael; Kesik, Jessica; Matzke, Burkhart; et al. (Trials, 2025)
Background: High levels of trait anger and aggressive behavior are common and problematic phenomena in patients with borderline personality disorder (BPD). In BPD, patterns of reactive aggression often lead to functional impairment affecting important areas of life. Despite the high burden on individuals and their social environment, there are no specific, cost‑effective treatments to reduce aggression in BPD. In previous studies, we and others have been able to infer specific biobehavioral mechanisms underlying patterns of reactive aggression in BPD that can be used as potential treatment targets. To address this, we developed a mechanism‑based anti‑aggression psychotherapy (MAAP) for the group setting that specifically targets the biobehavioral mechanisms underlying outward‑directed aggression in BPD. A previously conducted proof‑of‑concept study had suggested beneficial effects for this neglected group of patients. Methods: In this multicenter, confirmatory, randomized‑controlled‑clinical‑trial, MAAP, which consists of multifaceted, evidence‑based treatment elements adapted from other sophisticated treatment programs such as Dialectical Behavior Therapy and Mentalization‑Based Treatment, is tested for efficacy against a non‑specific supportive psychotherapy (NSSP) program focusing on non‑specific general factors of psychotherapy at seven different sites in Germany. Bothtreatment arms, based on one individual and 13 group therapeutic sessions (1.5 h per session, twice a week), are delivered over a period of 7–10 weeks. A total of N = 186 patients will be recruited, half of whom will be cluster‑randomized to MAAP. Outcomes are assessed at baseline, immediately, and 4, 12, 20, and 24 weeks post‑treatment using ecological momentary assessment, clinical interviews, questionnaires, and online tasks. Discussion: If proven superior, MAAP can be incorporated into standard psychiatric care, filling a critical gap in the current therapeutic landscape by offering a structured, cost‑effective, and evidence‑based treatment that directly targets the biobehavioral mechanisms underlying reactive aggression in BPD. By potentially improving clinical outcomes and reducing the burden of reactive aggression in BPD, MAAP could be beneficial for both individuals and their social environments. The study’s large, multicenter design enhances the generalizability of the results, making them more relevant for broader clinical applications.